Goodyera foliosa Var. Commelinoides (Orchidaceae): A New Record to Orchid Flora of Nepal - Raskoti, Bhakta B; Ale, Rita (Scientific World, 2010)
Goodyera foliosa (Lindl.) Benth. ex C. B. Clarke var. commelinoides (Fukuy.) F. Maek. (Orchidaceae) is first time reported from central Nepal as a new record to flora of Nepal. Detailed description, illustration and relevant notes are provided. Key words: Goodyera foliosa var. commelinoides; New record; Nepal. DOI: 10.3126/sw.v7i7.3824 Scientific World Vol.7(7) 2009 pp.47-48